Theory and practice of quality of experience in video services - Tiantian HE; Yankai LIU; Li SONG (Dianxin kexue)
As videos becoming the major sources of acquiring information in current era,consumers have raised their expectations for video quality experience,which has become the most critical competitiveness for video service providers.A thorough review of quality of experience (QoE) was presented,and then detailed analysis of video QoE and relevant no reference assessment methods were provided.Further,the standardization process of video QoE in China and the evaluation results of Chinese video services quality were introduced.Last but not the least,the characteristics of Chinese video services was summarized and advices of improvement were presented.